Prevalence and heritability of body dysmorphic symptoms in adolescents and young adults: a population-based nationwide twin study - Enander, Jesper; Ivanov, Volen Z.; Mataix-Cols, David; Kuja-Halkola, Ralf; Ljótsson, Brjánn; Lundström, Sebastian; Pérez-Vigil, Ana; Monzani, Benedetta; Lichtenstein, Paul; Rück, Christian (Psychological medicine, 2018)
Body dysmorphic disorder (BDD) usually begins during adolescence but little is known about the prevalence, etiology, and patterns of comorbidity in this age group. We investigated the prevalence of BDD symptoms in adolescents and young adults. We also report on the relative importance of genetic and environmental influences on BDD symptoms, and the risk for co-existing psychopathology. Prevalence of BDD symptoms was determined by a validated cut-off on the Dysmorphic Concerns Questionnaire (DCQ) in three population-based twin cohorts at ages 15 (n = 6968), 18 (n = 3738), and 20-28 (n = 4671). Heritability analysis was performed using univariate model-fitting for the DCQ. The risk for co-existing psychopathology was expressed as odds ratios (OR). The prevalence of clinically significant BDD symptoms was estimated to be between 1 and 2% in the different cohorts, with a significantly higher prevalence in females (1.3-3.3%) than in males (0.2-0.6%). The heritability of body dysmorphic concerns was estimated to be 49% (95% CI 38-54%) at age 15, 39% (95% CI 30-46) at age 18, and 37% (95% CI 29-42) at ages 20-28, with the remaining variance being due to non-shared environment. ORs for co-existing neuropsychiatric and alcohol-related problems ranged from 2.3 to 13.2. Clinically significant BDD symptoms are relatively common in adolescence and young adulthood, particularly in females. The low occurrence of BDD symptoms in adolescent boys may indicate sex differences in age of onset and/or etiological mechanisms. BDD symptoms are moderately heritable in young people and associated with an increased risk for co-existing neuropsychiatric and alcohol-related problems.